Disease Acceptance and Eudemonic Well-Being Among Adults With Physical Disabilities: The Mediator Effect of Meaning in Life - Szcześniak, Małgorzata; Świątek, Agata H.; Cieślak, Małgorzata; Świdurska, Daria (Frontiers in Psychology, 2020)
The acceptance of disability is recognized as one of the most frequently mentioned factors that plays a particularly significant role in subjective well-being. However, so far, only a very small amount of research has been undertaken to clarify how and why acceptance of illness relates to eudemonic well-being. Hence, comprehension of the direct and indirect effects underlying this relationship seems essential for interventions that increase the recovery of people with impairments and enhance their quality of life. The current research was aimed at investigating the association between acceptance of illness, meaning in life, and eudemonic well-being, as well as the possible mediatory effect of meaning in life on the relationship between acceptance of illness and well-being. The sample consisted of 102 participants (71% women) aged between 20 and 64 years. The respondents had a range of different impairments (e.g., cerebral palsy, neurological disorders, spinal muscular atrophy, and sight defects). The Acceptance of Illness Scale, the Meaning in Life Questionnaire, and the Ryff Scales of Psychological Well-Being were used. It was confirmed that acceptance of illness correlated positively and significantly with the presence of meaning, self-acceptance, positive relations, environmental mastery, personal growth, general well-being, cohesion, flexibility, communication, and family satisfaction. The presence of meaning mediated the relationship between acceptance of illness and general well-being with its four other dimensions: self-acceptance, environmental mastery, purpose in life, and personal growth. Conversely, the search for meaning did not have any mediatory effect on this relationship.